(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Along with the development of tourism in linguistics, the concept of tourism discourse has also received widespread development. Tourist discourse, that is, speech, has existed for a long time and is the object of linguistic and cultural research. This article talks about speech, its function, as well as the role and meaning of speech, that is, tourist discourse, in the field of tourism.